H2 plasma treatment at the p/i interface of a hydrogenated amorphous Si absorption layer for high‐performance Si thin film solar cells. (13th September 2012) - Lee, Czang‐Ho; Kim, Byoung‐June; Shin, Myunghun
ABSTRACT Plasma treatment (PT) of the buffer layer for highly H2‐diluted hydrogenated amorphous silicon (a‐Si:H) absorption layers is proposed as a technique to improve efficiency and mitigate light‐induced degradation (LID) in a‐Si:H thin film solar modules. The method was verified for a‐Si:H single‐junction and a‐Si:H/microcrystalline silicon (µc‐Si:H) tandem modules with a size of 200 × 200 mm2 (aperture area of 382.5 cm2) under long‐term light exposure. H2 PT at the p/i interface was found to eliminate non‐radiative recombination centers in the buffer layer, and plasma‐enhanced chemical vapor deposition at low radio‐frequency power was found to suppress the generation of defects during the growth of a‐Si:H absorption layers on the treated buffer layers. With optimized H2 PT of the a‐Si:H single‐junction module, the stabilized short circuit current and fill factor increased, and the stabilized open circuit voltage moves beyond its initial value. The results demonstrate 7.7% stabilized efficiency and 10.5% LID for the a‐Si:H single‐junction module and 10.82% stabilized efficiency and 7.76% LID for the a‐Si:H/µc‐Si:H tandem module. Thus, the growth of an a‐Si:H absorption layer on a H2 PT buffer layer can be considered as a practical method for producing high‐performance Si thin film modules. Copyright © 2012 John Wiley & Sons, Ltd.